Tropomyosin isoforms in chicken embryo fibroblasts: purification, characterization, and changes in Rous sarcoma virus-transformed cells (The Rockefeller University Press, 1985)
Seven polypeptides (a, b, c, 1, 2, 3a, and 3b) have been previously identified as tropomyosin isoforms in chicken embryo fibroblasts (CEF) (Lin, J. J.-C., Matsumura, F., and Yamashiro-Matsumura, S., 1984, J. Cell. Biol., 98:116-127). Spots a and c had identical mobility on two- dimensional gels with the slow-migrating and fast-migrating components, respectively, of chicken gizzard tropomyosin. However, the remaining isoforms of CEF tropomyosin were distinct from chicken skeletal and cardiac tropomyosins on two-dimensional gels. The mixture of CEF tropomyosin has been isolated by the combination of Triton/glycerol extraction of monolayer cells, heat treatment, and ammonium sulfate fractionation. The yield of tropomyosin was estimated to be 1.4% of total CEF proteins. The identical set of tropomyosin isoforms could be found in the antitropomyosin immunoprecipitates after the cell-free translation products of total poly(A)+ RNAs isolated from CEF cells. This suggested that at least seven mRNAs coding for these tropomyosin isoforms existed in the cell. Purified tropomyosins (particularly 1, 2, and 3) showed different actin-binding abilities in the presence of 100 mM KCl and no divalent cation. Under this condition, the binding of tropomyosin 3 (3a + 3b) to actin filaments was significantly weaker than that of tropomyosin 1 or 2. CEF tropomyosin 1, and probably 3, could be cross-linked to form homodimers by treatment with 5,5'- dithiobis-(2-nitrobenzoate), whereas tropomyosin a and c formed a heterodimer. These dimer species may reflect the in vivo assembly of tropomyosin isoforms, since dimer formation occurred not only with purified tropomyosin but also with microfilament-associated tropomyosin. The expression of these tropomyosin isoforms in Rous sarcoma virus-transformed CEF cells has also been investigated. In agreement with the previous report by Hendricks and Weintraub (Proc. Natl. Acad. Sci. USA., 78:5633-5637), we found that major tropomyosin 1 was greatly reduced in transformed cells. We have also found that the relative amounts of tropomyosin 3a and 3b were increased in both the total cell lysate and the microfilament fraction of transformed cells. Because of the different actin-binding properties observed for CEF tropomyosins, changes in the expression of these isoforms may, in part, be responsible for the reduction of actin cables and the alteration of cell shape found in transformed cells.